Electrification of Smart Cities - Lai, Chun Sing; Tsang, Kim-Fung; Wang, Yinhai (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
Electrification plays a key role in decarbonizing energy consumption for various sectors, including transportation, heating, and cooling. There are several essential infrastructures for a smart city, including smart grids and transportation networks. These infrastructures are the complementary solutions to successfully developing novel services, with enhanced energy efficiency and energy security. This Special Issue includes high-quality papers that address issues related to cutting-edge smart city technologies in the electrification process, including but not limited to the following: Electrification of building environments and transportation systems; Role and impact of smart grids for smart cities; ICT and IoT infrastructures with big data for smart city electrification; Market, services, and business models for smart city electrification; Standards and implementation for smart city electrification; Advanced smart grid technology integration in smart cities, such as energy storage, demand-side management, and distributed energy resources.